Development and Validation of Epilepsy Life Skills Guidelines for Primary School Learners and Teachers in Limpopo and Mpumalanga Provinces - Thendo Gertie Makhado; Rachel Tsakani Lebese; Maria Sonto Maputle (MDPI AG, 2023)
Epilepsy is a disorder that disturbs nerve cell activity in the brain, resulting in seizures. It was noted that it occurs mostly in children, especially at the primary school level, and could result from a genetic condition. The aim of this study was to develop and validate life skills education guidelines for primary school learners of Limpopo and Mpumalanga provinces in South Africa to educate them about epilepsy with the aim of reducing stigma and discrimination towards people with epilepsy. The guidelines were developed by adapting the World Health Organization (WHO) guideline development guide, which included the formulation of PICOS (population, intervention, comparison, outcome, study design) questions, conducting a systematic review of the literature, and using GRADE (grading of recommendations assessment, development, and evaluation) to develop evidence-based recommendations. The recommendations that informed the guideline development were that epilepsy education should be included in the primary school life skills curriculum to improve learners' understanding, attitudes, and skills related to epilepsy. This epilepsy education should be tailored to the needs of primary school learners and cover topics such as seizure recognition, management, medication, and coping strategies. Collaboration between healthcare providers, educators, and policymakers is crucial to developing culturally appropriate and evidence-based epilepsy education guidelines. Teachers and healthcare providers should also receive training on how to support learners living with epilepsy. The resulting guidelines provide clear and concise guidance on epilepsy education in life skills for primary school learners, caregivers, and teachers. The guidelines are expected to improve the quality of epilepsy life skills education and contribute to the overall well-being and inclusion of learners with epilepsy in Mpumalanga and Limpopo provinces, South Africa.